Kuwait : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This Selected Issues paper analyzes energy price reform in Kuwait. It emphasizes that Kuwait should take advantage of current low global energy prices to strengthen efforts to reform domestic energy prices. In the longer term, this would benefit growth by increasing efficiency in the economy and creating space for higher public and private investment. In the short-term, one-off effects on inflation should be manageable. Productive activities more sensitive to energy costs, particularly the transport sector, would be able to adjust to higher energy prices more easily if the reform is gradual.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet